Pengembangan Media Pembelajaran Playmat Interaktif Audio Visual sebagai Stimulasi Motorik Kasar pada Anak Usia Dini TK Laboratorium Universitas Negeri Malang - Alby Aruna; Khoirul Muanam; Purnomo Purnomo; Yerry Soepriyanto (Departement of Mathematics Education, 2024)
This study develops an interactive audio-visual playmat as a learning medium designed to stimulate gross motor skills in early childhood at the Kindergarten Laboratory of Universitas Negeri Malang. The methodology applied follows an educational system development model that includes needs analysis, product design and creation, as well as evaluation and revision. This medium aims to create an enjoyable learning experience that simultaneously stimulates the development of gross motor skills through a combination of audio and visual elements. These elements are strategically designed to activate gross motor responses such as jumping, running, and moving according to instructions. The interactive features of this playmat are designed to provide immediate feedback on children's physical movements, reinforcing the connection between sensory stimuli and motor response. Through a quantitative approach, this study makes a significant contribution to early childhood education, presenting a learning medium that is not only engaging but also effective in supporting the essential development of gross motor skills critical for children's physical growth and future motor skills.